Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ani13050796
|View full text |Cite
|
Sign up to set email alerts
|

Micro- and Macro-Algae Combination as a Novel Alternative Ruminant Feed with Methane-Mitigation Potential

Abstract: This study was conducted to provide alternative high-quality feed and to reduce methane production using a mixture of the minimum effective levels of Euglena gracilis, EG, and Asparagopsis taxiformis, AT. This study was performed as a 24 h in vitro batch culture. Chemical analysis demonstrated that EG is a highly nutritive material with 26.1% protein and 17.7% fat. The results showed that the supplementation of AT as a feed additive at 1 and 2.5% of the diet reduced methane production by 21 and 80%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…To mitigate the effects of climate change and improve agricultural production, the use of alternative feeds is proving to be a better option. Ahmed et al (18) showed that dietary supplementation of animal fodder with Asparagopsis taxiformis at 1 and 2.5% reduced methane production by 21 and 80% respectively, while the inclusion of Euglena gracilis in the diet at 10 and 25% reduced methane production by 4 and 11%, respectively, with no negative effect on fermentation parameters. Similarly, Gryllus bimaculatus and Bombyx mori reduced methane production by 18 and 16%, respectively, (87).…”
Section: Protecting the Environment Through The Use Of Alternative Feedsmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the effects of climate change and improve agricultural production, the use of alternative feeds is proving to be a better option. Ahmed et al (18) showed that dietary supplementation of animal fodder with Asparagopsis taxiformis at 1 and 2.5% reduced methane production by 21 and 80% respectively, while the inclusion of Euglena gracilis in the diet at 10 and 25% reduced methane production by 4 and 11%, respectively, with no negative effect on fermentation parameters. Similarly, Gryllus bimaculatus and Bombyx mori reduced methane production by 18 and 16%, respectively, (87).…”
Section: Protecting the Environment Through The Use Of Alternative Feedsmentioning
confidence: 99%
“…Furthermore, the results of Gbenou et al (17) revealed that the production of cows (Gir × Borgou) with the supplementation of 2 kg of sorghum meal resulted in a production of 3.3 kg of milk/day. According to Ahmed et al (18) the combination of micro-and macroalgae as ruminant feeds can replace the expensive conventional sources in animal diets and help to reduce feeding costs and livestock impacts on environmental. Biologically active compounds, such as flavonoids found in by-products of the winery industry and citrus fruits, are gaining attention for their ability to modulate the immune system of ruminants (19), due to their positive effects on milk quantity and quality (20).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the combination of microalgae ( 43 , 44 ) and of seaweeds ( 45 , 46 ) was reported to improve ruminant nutrition and milk quality. However, to the best of our knowledge, only one recent study evaluated the effects of a mixture of one microalgal ( Euglena gracilis ) and one seaweed ( Asparagopsis taxiformis ) species on in vitro ruminal fermentation parameters ( 47 ), and none of the studies have investigated the potential effects of combining two microalgal and two seaweed species. Thus, in this study, we assessed, for the first time, the effects of increasing supplementation levels (0, 5, 10, and 15%, DM basis) of a commercially available algal blend composed of two microalgal and two seaweed species on gas and methane production, pH, ammonia-N contents, and total VFA production and the proportion of individual VFA after 24 h of incubation with ruminal inocula obtained from cows fed forage-based diets with different proportions of two basal forages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in this study, we assessed, for the first time, the effects of increasing supplementation levels (0, 5, 10, and 15%, DM basis) of a commercially available algal blend composed of two microalgal and two seaweed species on gas and methane production, pH, ammonia-N contents, and total VFA production and the proportion of individual VFA after 24 h of incubation with ruminal inocula obtained from cows fed forage-based diets with different proportions of two basal forages. A wide range of algal supplementation levels are reported in the literature, with microalgae being included at lower levels (up to 10%, 26 ) and seaweeds at higher levels (up to 25%, 6 , 15 , 47 ). As the commercially available algal blend used in the present study was composed of both microalgae and seaweeds, low (5%), average (10%), and high (15%) supplementation levels were assessed to gain further insights into the potential of this non-conventional and sustainable feed in ruminant nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…30 Algae are classified into microalgae and macroalgae. 31 It is estimated that the number of species of algae is between one and ten million, and the majority are composed of microalgae. 32 Macroalgae, referred to as seaweeds, are multicellular, structurally complex and can be counted with the naked eye (sizes of up to 60 m in length), while a microscope is needed to observe microalgae (measuring about 3–20 μm), which are single-celled (unicellular) or form single colonies and may be prokaryotic or eukaryotic types.…”
Section: Microalgae As a Raw Materials For The Green Synthesis Of Npsmentioning
confidence: 99%